TOWARD RURAL SUSTAINABLE PHOTOVOLTAICS DEVELOPMENT IN INDONESIA THE EFFECTS OF SOCIOECONOMIC BENEFIT, INFORMATION ACCESS, AND FINANCING FACILITIES TO THE SUSTAINABILITY OF PHOTOVOLTAICS TECHNOLOGY APPLICATIONS - I Wayan Sujana (Universitas Trisakti, 2011)
The search for a substitute for fossil energy resources in view of the growing demand for environmentally friendly technologies for electricity generation, and the needs of the growing economics and population in Indonesia have increased the interest in photovoltaic as a long term, environmentally friendly and reliable energy technology. Although Indonesia outperformed its regional neighbors and joined China and India as the only G20 members posting growth during the 2009 economic crisis, Indonesia still struggles with poverty and unequal energy distribution. Fortypercent of Indonesian households are still not electrified and most of them live in the rural area.Indonesia is trying to introduce a modern electricity technology to rural population who cannot be served economically or in a timely manner by the conventional rural electrification system. For several decades, the electricity generation in Indonesia have been under the monopolistic management of national electric company, PLN controlled and funded by the government.Experience shows that PLN has for reasons of limited funding, inadequate capacity, and has been unable to service and ensure the expansion of the utility grid to most rural households.The utilization of a photovoltaic system is targeted to contribute to the rural electrification and contribute in total of one half percent to the domestic energy mix. The photovoltaic development in Indonesia is progressing very slowly. The goal to have 50 MWp of photovoltaic generating power in the year 2010 has not been accomplished. Current installed photovoltaic capacity is 10 MWp about 2.85 percent of the year 2025 target. This dissertation studies socio and economic viability, rural information access and financial facilities influences to the sustainability of photovoltaic system dissemination in the rural area of Indonesia